2019
DOI: 10.1186/s13601-019-0283-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asthma in adult population of southwestern Iran and its association with chronic rhinosinusitis: a GA2LEN study

Abstract: Background Asthma is recognized as a major public health concern in the world. The aim of this investigation was to evaluate the prevalence of asthma by using the Global Allergy and Asthma Network of Excellence (GA 2 LEN) questionnaire and examine its association with chronic rhinosinusitis, in the province of Bushehr, Southwestern of Iran. Methods In a cross-sectional, population-based study, a total of 5420 invited individuals, aged 15–65, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
2
8
1
Order By: Relevance
“…We show here that 32.2% patients reported a physician‐based diagnosis of asthma. This proportion of patients corresponds with previous studies evaluating the prevalence of asthma in CRS patients in tertiary centres, 8 but is higher than a recent report showing concomitant asthma in 16.3% of CRS patients in a population‐based study 18 . The higher proportion of patients with late‐onset compared to early‐onset asthma in our cohort confirms previous studies 7 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We show here that 32.2% patients reported a physician‐based diagnosis of asthma. This proportion of patients corresponds with previous studies evaluating the prevalence of asthma in CRS patients in tertiary centres, 8 but is higher than a recent report showing concomitant asthma in 16.3% of CRS patients in a population‐based study 18 . The higher proportion of patients with late‐onset compared to early‐onset asthma in our cohort confirms previous studies 7 .…”
Section: Discussionsupporting
confidence: 91%
“…A considerable amount of literature has been published demonstrating an association between asthma and CRS, especially with the CRSwNP phenotype 7,8,18 . We show here that 32.2% patients reported a physician‐based diagnosis of asthma.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have reported that CRS is closely associated with the incidence of BA. [ 2 , 14 , 15 ] Chung et al demonstrated that the odds ratio of patients with CRS was significantly higher than those without CRS. And CRS had an increased prevalence of various comorbidities, where asthma ranked first.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] What is more, according to Ostovar et al, 57.3% of subjects with asthma reported having CRS, which indicated that there was an association between CRS and asthma. [ 15 ] For the relationship between CRS and the severity of asthma, Matsuno et al only demonstrated a significant correlation between the asthma severity and sinus morphologic abnormalities in patients with and without sinusitis, which cannot prove sinus disease could directly affect the intensity of asthma. [ 16 ] Similarly, the CT findings of Bresciani study suggested that CRS was not related to the severity of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies based on more comprehensive disease features are required to identify asthma phenotypes in population-based studies. In Southwestern Iran, a study assessed using the GA 2 LEN questionnaire showed that the current prevalence of asthma in adult population is 8.9% and asthma is often associated with chronic rhinosinusitis [ 38 ].…”
Section: Asthmamentioning
confidence: 99%